Evolution of 2014/15 H3N2 Influenza Viruses Circulating in US: Consequences for Vaccine Effectiveness and Possible New Pandemic - Veljkovic, Veljko; Paessler, Slobodan; Glisic, Sanja; Prljic, Jelena; Perovic, Vladimir R.; Veljkovic, Nevena; Scotch, Matthew (Frontiers in Microbiology, 2015)
A key factor in the effectiveness of the seasonal influenza vaccine is its immunological compatibility with the circulating viruses during the season. Here we propose a new bioinformatics approach for analysis of influenza viruses which could be used as an efficient tool for selection of vaccine viruses, assessment of the effectiveness of seasonal influenza vaccines, and prediction of the epidemic/pandemic potential of novel influenza viruses.